Synthesis, characterization, conductivity and sensor application study of polypyrrole/silver doped nickel oxide nanocomposites. Issue 8 (3rd August 2018) - Ramesan, M. T.; Santhi, V.
Abstract: Conducting polymer composites of polypyrrole (PPy) and silver doped nickel oxide (Ag-NiO) nanocomposites were synthesised by in situ polymerisation of pyrrole with different contents of Ag-NiO nanoparticles. The formation of nanocomposites were studied by Fourier transform infrared (FTIR) and UV–vis spectroscopy, field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and AC and DC conductivity measurements. The sensitivity of ammonia gas through the nanocomposite was analysed with respect to different contents of nanoparticles. Spectroscopic studies showed the shift in the absorption bands of polymer nanocomposite than that of pure PPy indicating the strong interaction between the nanoparticles and polymer chain. FESEM revealed the uniform dispersion of nanoparticles with spherically shaped metal oxide particles in PPy matrix. The XRD pattern indicated a decrease in amorphous domain of PPy with increase in loading of nanoparticles. The higher thermal stability and glass transition temperature of polymer nanocomposites than that of pure PPy were revealed from the TGA and DSC respectively. The dielectric properties, DC and AC conductivity of nanocomposites were much higher than PPy and these electrical properties increases with the loading of nanoparticles. The nanocomposites showed an enhancement in sensitivity towards ammonia gas detection than PPy. Abstract :